A new promising Ni-MOF superstructure for high-performance supercapacitors. Issue 12 (17th January 2020) - Yang, Chengyu; Li, Xiaoyu; Yu, Ling; Liu, Xingjiang; Yang, Jie; Wei, Mingdeng
Abstract : A layered structural Ni-MOF nanosheet has been obtained, exhibiting capacitances of 1518.8 F g −1 at 1 A g −1 and 244 mF cm −2 at 0.5 mA cm −2 as electrodes for supercapacitor and flexible all-solid-state asymmetric supercapacitor, respectively. Abstract : A new layered structural Ni-MOF nanosheet has been successfully synthesized and used for the first time as an electrode for a supercapacitor and a flexible all-solid-state asymmetric supercapacitor, exhibiting capacitances of 1518.8 F g −1 at 1 A g −1 and 244 mF cm −2 at 0.5 mA cm −2, respectively.